2011
DOI: 10.1186/1475-2875-10-86
|View full text |Cite
|
Sign up to set email alerts
|

Success of Senegal's first nationwide distribution of long-lasting insecticide-treated nets to children under five - contribution toward universal coverage

Abstract: BackgroundIn 2009, the first national long-lasting insecticide-treated net (LLIN) distribution campaign in Senegal resulted in the distribution of 2.2 million LLINs in two phases to children aged 6-59 months. Door-to-door teams visited all households to administer vitamin A and mebendazole, and to give a coupon to redeem later for an LLIN.MethodsA nationwide community-based two-stage cluster survey was conducted, with clusters selected within regions by probability proportional to size sampling, followed by GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 9 publications
2
58
1
Order By: Relevance
“…Recent work by [18] and [19] proposed a number of ITN coverage measures related to the ownership and use of nets at individual or household level. Five indicators have been assessed in the study and only one suggested a reduction in malaria risk with increasing coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by [18] and [19] proposed a number of ITN coverage measures related to the ownership and use of nets at individual or household level. Five indicators have been assessed in the study and only one suggested a reduction in malaria risk with increasing coverage.…”
Section: Discussionmentioning
confidence: 99%
“…The included intervention studies evaluated two main channels for delivering ITNs to pregnant women: campaign delivery (non-targeted) [89],[92][94] and routine delivery to pregnant women through ANC services (targeted), with three alternative mechanisms evaluated at ANCs: distribution of free nets with [95]–[97] or without social marketing [98],[99], and distribution of subsidised vouchers [83],[84],[100][102]. One study compared the impact of ANC delivery alone versus ANC delivery plus community-based distribution of subsidised nets in Niger (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Campaign delivery of ITNs to households with pregnant women [89], households with children under 5 y [94], or poor households [93] had limited impact on increasing coverage among pregnant women with one exception, which was a campaign in Senegal that delivered ITN vouchers to all households with children under 5 y, alongside vitamin A and mebendazole (an anthelmintic) [92] (49.2% versus 28.5% ITN coverage in intervention versus control groups, respectively; no statistical analysis reported). In a comparison study in Tanzania, the Tanzania National Voucher Scheme, which provides a voucher subsidy to pregnant women at ANCs, which is then used to purchase an ITN from a contracted retailer, achieved greater coverage than a 3-d mass campaign targeting ITNs to households with infants, based on the assumption that infants sleep with their mothers, a common practice in this setting, or ITNs sourced from retailers [94].…”
Section: Resultsmentioning
confidence: 99%
“…The usual subsidized price was 1000 FCFA (USD2). The last campaign also included a series of communication interventions to advertise the campaign and to increase awareness of the importance of using bednets (Thwing et al, 2011).…”
Section: The Senegalese Contextmentioning
confidence: 99%